Dementia wellbeing and COVID‐19: Review and expert consensus on current research and knowledge gaps. (27th May 2021) - Liu, Kathy Y.; Howard, Robert; Banerjee, Sube; Comas‐Herrera, Adelina; Goddard, Joanne; Knapp, Martin; Livingston, Gill; Manthorpe, Jill; O'Brien, John T.; Paterson, Ross W.; Robinson, Louise; Rossor, Martin; et al.
Abstract: Objectives: In response to a commissioned research update on dementia during the COVID‐19 pandemic, a UK‐based working group, comprising dementia researchers from a range of fields and disciplines, aimed to describe the impact of the pandemic on dementia wellbeing and identify priorities for future research. Methods: We supplemented a rapid literature search (including unpublished, non‐peer reviewed and ongoing studies/reports) on dementia wellbeing in the context of COVID‐19 with expert group members' consensus about future research needs. From this we generated potential research questions the group judged to be relevant that were not covered by the existing literature. Results: Themes emerged from 141 studies within the six domains of the NHS England COVID‐19 Dementia Wellbeing Pathway: Preventing Well, Diagnosing Well, Treating Well, Supporting Well, Living Well and Dying Well. We describe current research findings and knowledge gaps relating to the impact on people affected by dementia (individuals with a diagnosis, their carers and social contacts, health and social care practitioners and volunteers), services, research activities and organisations. Broad themes included the potential benefits and risks of new models of working including remote healthcare, the need for population‐representative longitudinal studies to monitor longer‐term impacts, and the importance of reporting dementia‐related findings within broader health and care studies. Conclusions: The COVID‐19 pandemic has had a disproportionately negative impact on people affected by dementia. Researchers and funding organisations have responded rapidly to try to understand the impacts. Future research should highlight and resolve outstanding questions to develop evidence‐based measures to improve the quality of life of people affected by dementia. Key Points: The COVID‐19 pandemic has had a disproportionately negative impact on people affected by dementia, dementia services and research. Further research on the impacts of the pandemic is needed, and directions for future work are identified in this study. It is important to explore the potential benefits and risks of remote health and care, design inclusive and longitudinal studies to monitor longer‐term impacts, and report dementia‐specific findings within broader studies.